ASUPAN TINGGI NATRIUM DAN LAMA MENONTON TV SEBAGAI FAKTOR RISIKO HIPERTENSI OBESITIK PADA REMAJA AWAL - Destiany, Vindy; Sulchan, Muhammad (Departemen Ilmu Gizi, Fakultas Kedokteran, Universitas Diponegoro, 2012)
Background : Obesitic hypertension not only occurred in adults but also in adolescents. The prevalence of obesitic hypertension has increased in recent years. Consumption of high sodium foods and watching tv are risk factors were thought to cause obesitic hypertension in adolescents. The study aims to analyze consumption of high sodium foods and watching tv habits as risk factors for obesitic hypertension in early adolescents. Methods: This study used case control design with a comparator (38 cases and 38 controls). Obesity is determined by weight percentile for age and hypertension percentile determined by age, sex, and height. Sodium intake obtained by semi quantitative FFQ and watching tv habits used watching tv habits questionnaire. Results: The prevalence of obesitic hypertension is 7,5%. Consumption of high sodium foods have a significant correlation with incident of obesitic hypertension (p=0,001; OR=7,906) while watching tv habits hasn’t significantly increases incident of obesitic hypertension but this study show that it has correlation (p=0,648; OR=1,23).. Conclusion: T he study concludes that consumption of high sodium foods and watching tv habits are risk factors of obesitic hypertension occurrence on early adolescents. The multitude of consumption of high sodium foods and watching tv habits factors is respectively 7,9 times and 1,23 times.